A secure, anonymous and verifiable E-Voting system - Ooi, Elynn (2020)
This project is an online voting system that involve some network security which ensure a more secure, anonymous and verifiable E-Voting System. Readers will be able to gain some knowledges regarding the types of existing voting system and their vulnerabilities. The problem being emphasized in this project is regarding the security, anonymity and verification issues in an E-Voting System. These issues are serious security threat during the election process as it may affect the accuracy and reliability of the election result. Therefore, this paper studies the disadvantages of the existing voting system by looking through the method used by the society. Furthermore, this paper also proposes a more secure voting system which uses some encryption and hashing algorithms in order to solve the negative impacts of the existing voting systems. Besides that, it will also ensure that the identity of the voters is not traceable and the votes casted are verifiable by the voters themselves to prevent bogus votes. In short, a more accurate and reliable election result can be produced by the implementation of proposed solution.